Metode Pembelajaran Aqidah di Sekolah Menengah Atas - MOH ISMAIL; M Masrur Huda (EDUCATIO : Journal of Education, 2017)
The purpose of this study is to know what methods are applied in the learning of Aqidah. The type of research used is Field research that is qualitative. The result of this research is a method used in learning is very varied. So it can improve the quality of education by improving the learning methods that have been evaluated